Rwandan primary healthcare providers' perception of their capability in the diagnostic practice - Ditte L. Weber; Vincent K. Cubaka; Per Kallestrup; Susanne Reventlow; Michael Schriver (AOSIS, 2020)
Background: Skill-mix imbalance is a global concern for primary healthcare in low-income countries. In Rwanda, primary healthcare facilities (health centres, HCs) are predominantly led by nurses. They have to diagnose a multitude of health complaints. Whether they feel capable of undertaking this responsibility has yet to be explored. Aim: This study explored how healthcare providers (HPs) at Rwandan HCs perceived their capability in the diagnostic practice. Setting: Rural and urban HCs in Muhanga district, Rwanda. Method: Qualitative, semi-structured interviews with nurses and clinical officers, and observations of consultations were made. Findings were analysed thematically. Results: Rwandan HPs were confident in their competences to perform diagnostic procedures although nurses felt that the responsibilities lay beyond their professional training. Clinical officers believed that their professional training prepared them to function competently and autonomously in the diagnostic practice, although all HPs experienced a high dependency on medical history taking, physical examination and laboratory tests for reaching a diagnosis. Resource constraints (time, rooms and laboratory tests) were seen as a barrier to perform diagnostic tasks optimally, and HPs experienced in-service training and supervision as insufficient. They increased their diagnostic competences through work experience, self-learning and supportive peer collaboration. Conclusion: Clinical officers perceived themselves as capable in the diagnostic practice. Nurses may compensate for insufficient school training through in-service learning opportunities and feel capable in the diagnostic practice. Formative mentorship schemes and tailored education may prove valuable, but further research on how to improve HPs' diagnostic capability in Rwanda's primary healthcare sector is needed.